A simple broth-disk method to determine the minimum inhibitory concentration of ceftriaxone on Salmonella enterica serovar typhi and paratyphi - Bhat K; Tripathy Amruta; Rajagopal Rajasree; Ramachandran Sreeja (Wolters Kluwer Medknow Publications, 2009)
Background and Purpose: Resistance to fluoroquinolones and cephalosporins is a major problem with Salmonella enterica serovar Typhi and Paratyphi. An accurate determination of antibiotic susceptibility requires tests for minimum inhibitory concentration (MIC) of antibiotics. We describe a simple broth-disk method to determine the MIC of ceftriaxone on S. typhi and S. paratyphi . Materials and Methods: Sixteen strains of S. typhi and two strains each of S. paratyphi A and S. paratyphi B were used in the study. The MIC of ceftriaxone was determined using the simple broth-disk method and the conventional broth macrodilution method and the results were compared. Results: All salmonella strains were susceptible to ceftriaxone. The results of the broth-disk and the conventional broth macrodilution method were similar. Conclusion: The broth-disk method is a simple, reliable and cost-effective method to determine the MIC of ceftriaxone on S. typhi and S. paratyphi A.